2006
DOI: 10.4028/www.scientific.net/msf.514-516.1020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Weight and Crystallinity of Poly(L-Lactic Acid) on the Adhesion and Proliferation of Human Osteoblast Like Cells

Abstract: The molecular weight and crystallinity of systems based on poly(L-lactic acid) PLLA is an important issue as it can influence, besides the general physical properties of the polymer, the patterns of cell adhesion, proliferation and cell morphology. The objective of the present study was to evaluate how crystallinity and molecular weight of PLLA influence the referred parameters. Four conditions were tested: low molecular weight amorphous and semi-crystalline PLLA disks, and high molecular weight amorphous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
(32 reference statements)
2
15
0
Order By: Relevance
“…It is interesting to notice at this point that the variations in the degree of crystallinity in PLLA films does not imply significant variations either in the contact angle (74º +/-3 for 10% and 67% crystalline samples) [41] nor in the stiffness (Young Modulus of 3.4+/-0.3 and 3.5+/-0.2 GPa for 7% and 40-50% crystalline samples) [42]. When the amorphous electrospun fibrils crystallize their stiffness and surface energy increase [22,43], and at the same time surface nano-roughness is expected to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to notice at this point that the variations in the degree of crystallinity in PLLA films does not imply significant variations either in the contact angle (74º +/-3 for 10% and 67% crystalline samples) [41] nor in the stiffness (Young Modulus of 3.4+/-0.3 and 3.5+/-0.2 GPa for 7% and 40-50% crystalline samples) [42]. When the amorphous electrospun fibrils crystallize their stiffness and surface energy increase [22,43], and at the same time surface nano-roughness is expected to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Sladago et al [ 59 ] reported a study to evaluate how crystallinity and molecular weight of PLLA influenced the patterns of cell adhesion, proliferation, and cell morphology parameters. Four conditions were tested: low molecular weight amorphous and semi-crystalline hot-pressed PLLA disks (PLLA1-A and PLLA1-SC), and high molecular weight amorphous and semi-crystalline hot-pressed PLLA disks (PLLA2-A and PLLA2-SC).…”
Section: Effect Of Pla Polymers Crystallinity On Cellsmentioning
confidence: 99%
“… SEM micrographs of human osteoblasts like cells after two weeks in culture ( a ) amorphous PLLA1; ( b ) semi-crystalline PLLA1; ( c ) Cell viability measured from the optical density (O.D.) at 490 nm; and ( d ) Cell proliferation assays on SaOS-2 cells grown on PLLA disks, (PLLA1—low molecular weight; PLLA2—high molecular weight; A—amorphous; SC—Semi-crystalline) [ 59 ]. …”
Section: Figurementioning
confidence: 99%
“…This polymer is also an environmentally compostable material and, hence, it has been proposed for eco-friendly applications [3,4]. PLLA may crystallize slowly [7][8][9], and it is well-known that the presence of crystallinity has a profound impact on its physical properties, degradation profile and cell behavior [10][11][12][13][14][15]. Different techniques may be used to screen the evolution of the crystalline fraction during crystallization.…”
Section: Introductionmentioning
confidence: 99%